Everyday Life Experiences of Independence in Women with Rheumatoid Arthritis (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2017)
Background. Rheumatoid arthritis (RA) is an incurable disease which affects the human body and day to day activities. Diffcultly completing daily tasks is the main problem associated with rheumatoid arthritis. This chronic disease causes a large number of restrictions when dealing with daily life. Restrictions can be simple as having diffculty with basic activities such as looking after themselves and their homes, and too diffcult in more advanced tasks which require greater effort. These restrictions not only affect the ability of the individual to complete daily tasks but can also have a negative impact on the individual’s emotional and social relationships and their overall quality of life. The aim – describe everyday life experiences of women with rheumatoid arthritis. Methods. A qualitative study was carried out where 3 women who suffered with rheumatoid arthritis were interviewed. The average duration of the disease was 15 years and the average age of women interviewed was 56 years. The interview consisted of 7 questions, including how independent women were in conducting daily activities when they had the disease. The study was carried out in February– April, 2017. Each woman was interviewed individually and the conversation was recorded with a Dictaphone and the conversation was then transcribed. Data were analysed applying the method of content analysis. All the data was then analysed and later sorted in subcategories, which were then grouped into larger categories. The interview period lasted from 30 minutes up to 1 hour. Results. The results revealed that women had problems with the symptoms of illness in their daily lives such as dealing with self-care, clothing, food and work. Conclusions. 1) Women with rheumatoid arthritis had changes in daily activities in the following areas: personal hygiene, dressing and undressing, preparing food, having problems showering, the pain they had in the shoulder did not allow them to complete daily activities as desired. 2) As the conditions of the joints worsen, everyday activities become more painful, performed slower and require greater effort, it becomes diffcult to grab and hold small objects. 3) Activities performed by individuals with rheumatoid arthritis are decreased due to the presence of symptoms, but women took measures to complete these activities easier.Keywords: rheumatoid arthritis, independence, life experiences, daily activities, occupational therapy.